A cross the wide river - Hewitt, William 1947- (Albuquerque : University of New Mexico Press, 2003)
Straddling the white world where he lives and attends school and the Winnebago reservation where he spends summers with his grandparents, a boy must face discrimination head-on when a whites-only cemetary refuses to bury his father, a Korean War hero.
Includes bibliographical references (p. 95-96).
Keywords: Discrimination -- Fiction; Winnebago Indians -- Fiction; Indians of North America -- Iowa -- Fiction; Iowa -- History -- 20th century -- Fiction